Management control systems - Anthony, Robert N.; Govindarajan, Vijay (Chicago : Irwin Inc., 1995)
The book provides concepts, text, and cases for a course in management control systems.
Part 1 : The Management control environment -- Part 2 : The Management control process -- Part 3 : Variations in management control
Includes index.
Keywords: INDUSTRIAL MANAGEMENT